Proceedings of 1st International Conference of Law and Justice - Good Governance and Human Rights in Muslim Countries: Experien 2018
DOI: 10.2991/iclj-17.2018.39
|View full text |Cite
|
Sign up to set email alerts
|

Global Hijriyah Calendar As Challenges Fikih Astronomy

Abstract: Abstract-Unification

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…There are many other calendars on the basis of different visibility or presence criteria of new moon e.g. [6] and [7]. The Ministry of Science and Technology, Pakistan has also issued a criterion and a calendar [8].…”
Section: Figure 1: New Moon and Crescent Formationmentioning
confidence: 99%
“…There are many other calendars on the basis of different visibility or presence criteria of new moon e.g. [6] and [7]. The Ministry of Science and Technology, Pakistan has also issued a criterion and a calendar [8].…”
Section: Figure 1: New Moon and Crescent Formationmentioning
confidence: 99%
“…A study produced findings on the importance of standardizing the basis for calculating each country's beginning of the Hijriyah month or the unification of the world Islamic calendar (Ilyas, 2016). Another study puts more emphasis on the aspect of fiqh, namely astronomical fiqh, especially relating to the time of worship, which is based on the movement of the moon and sun (Angkat, 2017;Maskufa, 2018). Fadholi (2018) research indicated that Islamic organizations in Indonesia emphasize the criteria for the visibility of the hilāl of MABIMS as a guide in preparing the Hijri calendar in Indonesia.…”
Section: Introductionmentioning
confidence: 99%